2018
DOI: 10.1007/s10696-018-9321-2
|View full text |Cite
|
Sign up to set email alerts
|

A decision support system and a mathematical model for strategic workforce planning in consultancies

Abstract: Strategic staff planning in consultancies is a major problem that directly affects the firm's performance and capacity for dealing with projects appropriately. Furthermore, the decisions taken now will have long term consequences, because consultants are highly qualified workers who need very long learning periods to achieve enough expertise. In other words, the size and composition of the future workforce depends on the decisions taken today. It is important to underline that the system anticipates future cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Li et al [26] identified two main types of approaches in the literature to tackle manpower planning problems: exploratory models and normative models. Generally, the approaches deal either with long-term manpower (strategic) planning [27,28] or short-term staff scheduling (see Van der Bergh et al [29] for a literature review), but integrated approaches or tools are even scarcer. Among them, Henderson et al [30] introduced an integrated approach for manpower planning in a post office in which a simulation model is used to size the staff.…”
Section: Existing Integrated Planning Frameworkmentioning
confidence: 99%
“…Li et al [26] identified two main types of approaches in the literature to tackle manpower planning problems: exploratory models and normative models. Generally, the approaches deal either with long-term manpower (strategic) planning [27,28] or short-term staff scheduling (see Van der Bergh et al [29] for a literature review), but integrated approaches or tools are even scarcer. Among them, Henderson et al [30] introduced an integrated approach for manpower planning in a post office in which a simulation model is used to size the staff.…”
Section: Existing Integrated Planning Frameworkmentioning
confidence: 99%
“…The numerical illustration proves the model efficiency. Strategic staff planning affects a firm performance [13]. An mathematical optimization model is proposed for solving staff planning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By contrast, this paper considers workforce planning as a centralized decision-making process consisting of sequential steps which may be grouped into three main processes: demand modeling, shift rostering and disruption handling (Defraeye and Van Nieuwenhuyse, 2016) Figure 1 provides an overview of these high-level processes with their detailed steps. Note that the strategic level of decision-making, primarily concerned with manpower planning, is also relevant in workforce planning (Llort et al, 2019). As discussed by Komarudin et al (2013), decisions at this level have a significant influence upon the others, and vice versa.…”
Section: Introductionmentioning
confidence: 99%